Public-Private Partnership in the Framework of Waste Management into Electrical Energy in Jatibarang Landfill, Semarang City - Azaria Eda Pradana; Retno Sunu Astuti; Budi Puspo Priyadi (Universitas Muhammadiyah Malang, 2020)
In recent years, especially in big cities, the waste problem has begun to be addressed through a private-public cooperation scheme that is supported by technological upgrades. The purpose of this research is to analyze the public-private cooperation mechanism that involves processing waste into electrical energy at Jatibarang Landfill, Semarang, and to identify the inhibiting factors using the theory of implementation